Dinâmica do crescimento do consórcio trevo-persa e azevém anual sob diferentes intervalos de desfolhas - Sganzerla, Daiane Cristina (2013)
Morphogenetic, structural and productive characteristics, were avaliated in a mixed pasture of persian clover (Trifolium resupinatum L. var. resupinatum Gib. & Belli cv. Kyambro) and italian ryegrass (Lolium multiflorum Lam cv. Comum) under different defoliation intervals. The experiment was conducted at the Embrapa Clima Temperado, Capão do Leão, RS. The treatments consisted of four defoliation intervals (determined according to the time of onset of 2,5; 3,5; 4,5 and 5,5 leaves on the persian clover) in two years of evaluation (2009 and 2010 ). We used a complete randomized blocks, with six replications. Defoliation was performed by grazing with lactating cows of the Jersey breed, under rotational stocking. The variables analyzed included: rate of leaf appearance, phyllochron, number of live leaves, dead and senescent, sward height and plant, length of branches / tillers, dry matter production, leaf area, leaf area index and rate dry matter accumulation. Higher rates of leaf appearance were found in shorter intervals between defoliation for both clover and for ryegrass. For persian clover larger intervals provided greater number live leaves. As for ryegrass, greater live leaves found in shorter intervals between defoliation. The leaf area index of pasture and persian clover was higher in the interval of 5,5 leaves in the years 2009 and 2010. In 2009 the highest values of leaf area were obtained in intervals of 3,5 and 4,5 leaves and there was no effect of the intervals between defoliation in 2010 on this variable. Higher intervals provided higher sward height and plants height and also length of tillers and branches. The dry matter yield of persian clover was higher in 2010 while for ryegrass higher production was found in 2009, and the total dry matter production was higher in the interval of 5,5 leaves. The rate of dry matter accumulation was higher in the interval of 5,5 leaves in 2009 and in the interval of 2,5 leaves in 2010. Higher intervals between defoliation provide higher LAI values, sward height and dry matter production. Morphogenetic, structural and productive characteristics of a mixture persian clover and ryegrass are modified by defoliation intervals, demonstrating the phenotypic plasticity of the species. Are recommended defoliation intervals of to 3,5 appeared leaves in a mixed pastures of persian clover and ryegrass to enable a greater number of live leaves attached to a lower stems elongation, characteristics desirable from the standpoint of animal production.